A minireview of pharmacotherapy of type 2 diabetes – drugs and mechanisms (Research, Society and Development, 2022)
Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder that originates from numerous pathogenic mechanisms, all of which result in hyperglycemia. This disease is a major cause of morbidity and mortality worldwide. Effective prevention and treatment strategies for T2DM are therefore necessary. The purpose of this review was to summarize the pharmacotherapy for patients with T2DM by discussing its pathophysiology, the therapeutic classes used in treatment strategies, as well as the mechanisms of action for each one. A literature review was conducted by searching Google Scholar, PubMed, and Science Direct databases using the search terms: type 2 diabetes mellitus, insulin, AMPK, antidiabetic drugs, incretin, SGLT2, and biguanides covering studies up to 2022. The review identified and included studies including qualitative, original research articles, and randomized controlled trial designs. The results of this study are divided into drugs that increase insulin sensitivity (e.g., biguanides, and thiazolidinediones), secretagogues (e.g., sulfonylureas, and meglitinides or glinides), incretin mimetics drugs (e.g., GLP-1 receptor agonists, and DPP-4 inhibitors), drugs that cause glycosuria (e.g., SGLT2 inhibitors), drugs that prevent glucose absorption (e.g., α-glucosidase inhibitor), and insulin. This allows the readers to understand each process while keeping the paper concise.